GENOTYPING AND PHYLOGENETIC ANALYSIS OF FRANCISELLA TULARENSIS HOLARTICA STRAINS ISOLATED ON THE TERRITORY OF UKRAINE - Golubyatnykov, M.I.; Bachynska, O.V.; Dzurtubaieva, H.M.; Melnyk, O.A.; Hrytsenko, K.S.; Gerasymenko, O.A.; Sovirda, O.S. (World of Medicine and Biology, 2024)
For the first time in Ukraine, a detailed genotypic characterization of a collection of strains (197) of Francisella tularensis holarctica, isolated both against the background of epidemic complications and in the inter-epidemic period, was provided. The sources of the pathogen were: ticks (56.30 %), small mammals (22.30 %) and the aquatic environment (19.30 %), three isolates were isolated from humans (2.03 %). A significant genetic diversity of the pathogen was found on the territory of Ukraine with the dominance of genotypes belonging to genogroup A (81.21 %), genogroups B and C were found in 11.68 % and 7.11 %, respectively, which distinguishes the genetic composition of the pathogen circulating in the territory of the majority European countries. A dendrogram was constructed based on PCR analysis of VNTR loci. the genetic distances between the isolates were calculated, and certain regularities regarding their molecular genetic polymorphism were also revealed. It was established that isolates belonging to genotypes of group C are the most genetically distant from group A. The genetic distance between group A and C isolates is 0.24. The difference in genetic distances between pathogens with genotypes A and B is minimal and amounts to 0.15, which may indicate their close relationship, although they were isolated in different years and in different regions of Ukraine. There is a tendency for the relatedness of isolates depending on belonging to a certain host and geographical origin, which indicates the combined influence of these factors on the processes of microevolution during the formation of the genotype.
Keywords: Francisella tularensis holartica; genetic polymorphism; phylogenetic analysis; the risk of activation; Ukraine